INTEGRASI NILAI-NILAI PENDIDIKAN ISLAM DAN MODERASI BERAGAMA DALAM MEMBANGUN KARAKTER REMAJA DI ERA MULTIKULTURAL: PERSPEKTIF PSIKOLOGI DAN SOSIAL KULTURAL - Novita Harini; Hamdan; Hidayat Ma’ruf; Ridhahani Fidzi (CV. Adiba Aisha Amira, 2025)
This article aims to examine the integration of Islamic education values and religious moderation in shaping adolescent character in a multicultural era, from psychological and socio-cultural perspectives. The multicultural era, characterized by cultural, religious, and social diversity, presents both opportunities and challenges for adolescent identity formation. In Indonesia, as a country with a Muslim-majority population, Islamic education plays a strategic role in fostering a younger generation that is moderate, tolerant, and inclusive. However, challenges such as globalization, social media, and extremist narratives often lead adolescents to experience identity conflicts and moral dilemmas. The research method employed is library research, gathering data from various primary sources such as books, journals, official documents, and articles related to Islamic education, religious moderation, and multiculturalism. The findings indicate that Islamic education values, such as tauhid (the oneness of God), akhlakul karimah (noble character), ibadah (worship), and scientific knowledge, can serve as spiritual and moral foundations supporting the principles of religious moderation, including tawassuth (moderation), tasamuh (tolerance), i’tidal (justice), and tawazun (balance). Systematic implementation of these values through formal education curricula and interactive religious programs has proven effective in enhancing tolerance and cross-cultural cooperation among adolescents. Therefore, Islamic education applied critically and contextually holds significant potential as a solution to address socio-cultural challenges and build adolescent character that is moderate, empathetic, and inclusive amidst the dynamics of a multicultural society.